BASIS gridded icedata 1963-1979 covering The Baltic Sea - Sahlberg, Jörgen (Finnish-Swedish Winter Navigation Research Board, 2019)
In 612 points icedata in coded form is stored in an ascii file. fi=66deg-r0.25deg lambda=7.5 deg + c0.5 deg The ice code covers temperature: TTTXXX ICECODE:ICDIC(C1C2C3C4C5) all described in BASIS A databank for Baltic sea ice and sea surface temperatures Norrköping 1981 (this paper will be available together with the data .set The datafile is called: BASIS_F.DAT This is a joint project between SMHI and FMI in a winter navigation program. Data have been extracted from reanalyzed ice and surface temperature maps with a frequency of two datsets (maps) a week. 16 seasons are covered. After 1979 a higher resolution has been created. There will be attempts to combine with this dataset at a later stage. The data file has been read with Matlab and mat files of ice concentration and the icecode. These files are also provided.

Se den engelska beskrivningen för mer information.
BASIS gridded icedata 1963-1979 covering The Baltic Sea
Keywords: ATMOSPHERE; OCEANS; SEA ICE; OCEAN TEMPERATURE; SEA SURFACE TEMPERATURE; SEA ICE; LEADS; ICE TYPES; ICE DEPTH/THICKNESS; ICE EDGES; ICE EXTENT; Climate Science; Klimatvetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap